The cost-effectiveness of an early interventional strategy in non-ST-elevation acute coronary syndrome based on the RITA 3 trial. Issue 6 (21st November 2007) - Henriksson, M; Epstein, D M; Palmer, S J; Sculpher, M J; Clayton, T C; Pocock, S J; Henderson, R A; Buxton, M J; Fox, K A A
Abstract : Background: Evidence suggests that an early interventional strategy for patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) can improve health outcomes but also increase costs when compared with a conservative strategy. Objective: The aim of this study was to assess the cost-effectiveness of an early interventional strategy in different risk groups from a UK health-service perspective. Design: Decision-analytic model based on randomised clinical trial data. Main outcome measures: Costs in UK Sterling at 2003/2004 prices and quality-adjusted life years (QALYs) combined into an incremental cost-effectiveness ratio. Methods: Data from the third Randomised Intervention Trial of unstable Angina (RITA 3) was employed to estimate rates of cardiovascular death and myocardial infarction, costs and health-related quality of life. Cost-effectiveness was estimated over patients' lifetimes within the decision-analytic model. Results: The mean incremental cost per QALY gained for an early interventional strategy was approximately £55 000, £22 000 and £12 000 for patients at low, intermediate and high risk, respectively. The early interventional strategy is approximately 1%, 35% and 95% likely to be cost-effective for patients at low, intermediate and high risk, respectively, at a threshold of £20 000 per QALY. The cost-effectiveness of early intervention in low-risk patients is sensitive to assumptions about the duration of the treatment effect. Conclusion: An early interventional strategy in patients presenting with NSTE-ACS is likely to be considered cost-effective for patients at high and intermediate risk, but this is less likely to be the case for patients at low risk.